Eksplorasi & Seleksi Cendawan Rizosfer Pada Tanaman Kelapa Sawit (Elaeis Guinnensis Jacq) yang Berpotensi Sebagai Entomopatogen - Ramadani, Iqbal; Vajri, Indri Yanil (Universitas Medan Area, 2025)
Oil palm (Elaeis guineensis Jacq) is a strategic plantation commodity in Indonesia that plays an important role in the national economy. However, the productivity of these plants is often hampered by pest attacks such as fireworms (Setora nitens) and horn beetles (Oryctes rhinoceros). So far, pest control has relied more on synthetic pesticides that have a negative impact on the environment and health. This study aims to explore the potential of local entomopathogenic fungi from oil palm rhizosphere soils as biological agents for pest control. The research was carried out through the stages of isolation, morphological characterization, and bioassay tests on Tenebrio molitor larvae. The results showed six mushroom isolates, namely Aspergillus sp., Beauveria sp., and Trichoderma sp. From the bioassay test, three isolates were pathogenic to the larvae, with the isolate Beauveria sp. (CRT 03) showed the highest mortality of 85%, LT₅₀ for 4.26 days, and mycosis 55.88%. These results show that Beauveria sp. CRT 03 has high potential as a local bioinsecticide. This research supports the development of sustainable pest control in oil palm plantations through the use of environmentally friendly biological agents.